Galling Insect Species Richness and Leaf Herbivory in an Abrupt Transition Between Cerrado and Tropical Dry Forest. (21st June 2016) - Silva, Jhonathan O.; Espírito-Santo, Mário M.; Fernandes, G. Wilson
Abstract : Galling species (GS) and leaf-chewing insects differ in resource use and sensitivity to microclimatic factors. We tested the effects of the harsh environmental, plant richness, and density on GS attack and the leaf damage inflicted by leaf-chewing insects along an abrupt transition between the savanna and tropical dry forest in Brazil. We found 134 GS on 406 trees belonging to 75 species in 30 sampled plots during the rainy season. Higher GS number was found in xeric habitats, according to the gradient: cerrado > transition > dry forest, whereas opposite pattern was found for the percentage of leaf area removed by insects. In general, plant richness and density significantly affected GS richness. On the other hand, herbivore responses to tree density (at intraspecific level) depended largely on host tree species evaluated. Our results provide evidence for the harsh environmental hypothesis on galling richness in xeric habitats, and plant species richness and density positively explained the increase in local GS richness. The high GS richness sampled demonstrates that more attention should be directed to the biodiversity and conservation of abrupt transition areas in cerrado, given their success and possible extensive radiation in there. In this perspective, the conservation of areas with higher plant species number and density may have primordial implications to preserve the diverse and specific GS richness associated to these close habitats.